AI, human dignity, and the right to learn: Educational equity for people with intellectual disabilities and SDG 4 - Dosary, Yasser Mubarak; Alanazi, Hani H; Algizani, Amira Mohamed; Abdellatif, Mohamed; Abdalrahman Elsayed, Elsayed; Ali, Nashat Abdeladl (Research Journal in Advanced Humanities, 2026)
Individuals with intellectual disabilities (ID) occupy a historically marginalized position within dominant educational and cultural structures, confronting compounded barriers to equitable, quality education that conventional instructional and counseling models have persistently failed to address — raising urgent questions about human dignity, epistemic justice, and the ethics of technological mediation in human development. Artificial intelligence (AI) has emerged as a potentially transformative tool for bridging these gaps, yet the evidence base remains fragmented. This systematic review, conducted following PRISMA 2020 guidelines, synthesizes findings from 50 peer-reviewed studies published between 2020 and 2025, examining the effectiveness, philosophical and ethical dimensions, and equity implications of AI-powered interventions for individuals with ID, situating these within broader humanities discourses on inclusion, autonomy, and the cultural politics of disability. Evidence is organized across seven outcome domains: academic skills, communication and language, career self-efficacy, emotional regulation, social integration, physical independence, and health–education integration. Results demonstrate the strongest empirical support for academic and communication outcomes, moderate evidence for career self-efficacy and emotional regulation, and limited evidence for the remaining domains. Key challenges include algorithmic bias, inadequate data governance, digital access inequities, exclusion of individuals with ID from participatory design, and a marked concentration of research within high-income countries—collectively undermining alignment with Sustainable Development Goal 4. Achieving equitable educational transformation requires coordinated investment in rigorous research design, inclusive participatory frameworks, regulatory reform, and educator capacity-building across diverse global contexts — grounded in a humanities-informed commitment to human rights, relational ethics, and the irreducible value of every learner's voice.